PERKEMBANGAN UMKM DENGAN FINANCIAL TECHNOLOGY DAN DIGITAL MARKETING SEBAGAI VARIABEL PREDIKTOR - Mikrad Mikrad; Agung Budi; Amalia Indah Fitriana (Universitas Muhammadiyah Tangerang, 2022)
AbstractThis study aims to analyze the influence of financial technology and digital marketing on the development of SMEs both partially and simultaneously in Cipondoh District. This research uses associative method with quantitative approach. The sample of this research is 83 respondents of SME actors from a population of 429 SMEs in Cipondoh District. Data collection techniques and tools are questionnaires and questionnaires. Descriptive data analysis technique was used to describe the responses of respondents and the distribution of data, while inferential statistical analysis was used to test the hypothesis. Data processing is assisted by Microsoft excel and SPSS software version 24. Based on the correlation test of Financial Technology (X1) and Digital Marketing (X2) with MSME Development (Y) of 69.4%, the remaining 30.6% is influenced by other variables (X) which is not studied (epsilon) but affects the development of SMEs (Y). The simultaneous influence of Financial Technology and Digital Marketing on the development of SMEs in Cipondoh District. Partially, Financial Technology and Digital Marketing each have a positive and significant impact on the development of SMEs in Cipondoh District.Keywords: Financial Technology, Digital Marketing, SME Development